Model Problem Based Learning dalam Pembelajaran Pendidikan Agama Islam pada Kurikulum Merdeka: Analisis Praktik Pembelajaran di SMAN 3 Kota Pekalongan - Urfah Islamia; Arditya Prayogi; Mohammad Syaifuddin; Riki Nasrullah (Universitas Nusantara PGRI Kediri, 2025)
The implementation of the Independent Curriculum demands a more contextual, participatory, and student-centered approach to Islamic Religious Education (ISE). One learning model deemed relevant to these demands is Problem-Based Learning (PBL). This study aims to analyze the implementation of the PBL model in Islamic Religious Education (PAI) learning under the Independent Curriculum at SMA Negeri 3 Pekalongan, encompassing aspects of planning, implementation, evaluation, and supporting and inhibiting factors. This study employed a qualitative approach with field research. Data collection techniques included in-depth interviews, learning observations, and documentation of teaching modules. Data analysis employed interactive analysis techniques that included data condensation, data presentation, and conclusion drawing, along with data validity testing through source and technique triangulation. The results of the study indicate that the implementation of PBL in ISE learning has been implemented systematically and in line with the principles of the Independent Curriculum, enhancing students' activeness, understanding, and critical thinking skills. The main supporting factors include curriculum flexibility, teacher competence, and the availability of learning resources, while inhibiting factors include low student self-confidence, suboptimal group cooperation, and less than conducive classroom conditions.